2001
DOI: 10.1080/02699050010013671
|View full text |Cite
|
Sign up to set email alerts
|

Biased responding: a case series demonstrating a relationship between somatic symptoms and impaired recognition memory performance for traumatic brain injured individuals

Abstract: Biased responding on the Sternberg Recognition Memory Test was observed in four patients with traumatic brain injury. None of these individuals met the Diagnostic and Statistical Manual's (DSM-IV) criteria for malingering. Individual recognition memory scores were high shortly after injury, declined to chance or below at the 6- and 12-month evaluations, and then showed substantial recovery by the 24-month evaluation. Recall memory performance actually declined slightly across this same 2-year period. Recogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Although earlier researchers (e.g., Ashendorf, Constantinou, & McCaffrey, 2004;Rees, Tombaugh, & Boulay, 2001) found no relationship between depression and ETF in non-litigating psychiatric participants, other more recent studies including non-litigating psychiatric patients (Dandachi-Fitzgerald et al, 2011;Gorissen, Sanz, & Schmand, 2005), compensation-seeking depressed participants (Green, 2009), non-litigating, non-compensation seeking TBI participants (Bierley et al, 2001), and compensation-seeking neurological participants (Armistead-Jehle, 2010;Rohling, Green, Allen, & Iverson, 2002;Stulemeijer et al, 2007;Suhr, Tranel, Wefel, & Barrash, 1997), have detected a relationship, but Schroeder and Marshall (2011) did not. Schroeder and Marshall (2011) have suggested that reliance on single SVT failure to indicate ETF might account for some of the inconsistent findings in this field and this will be further examined in the present study.…”
Section: Introductionmentioning
confidence: 90%
“…Although earlier researchers (e.g., Ashendorf, Constantinou, & McCaffrey, 2004;Rees, Tombaugh, & Boulay, 2001) found no relationship between depression and ETF in non-litigating psychiatric participants, other more recent studies including non-litigating psychiatric patients (Dandachi-Fitzgerald et al, 2011;Gorissen, Sanz, & Schmand, 2005), compensation-seeking depressed participants (Green, 2009), non-litigating, non-compensation seeking TBI participants (Bierley et al, 2001), and compensation-seeking neurological participants (Armistead-Jehle, 2010;Rohling, Green, Allen, & Iverson, 2002;Stulemeijer et al, 2007;Suhr, Tranel, Wefel, & Barrash, 1997), have detected a relationship, but Schroeder and Marshall (2011) did not. Schroeder and Marshall (2011) have suggested that reliance on single SVT failure to indicate ETF might account for some of the inconsistent findings in this field and this will be further examined in the present study.…”
Section: Introductionmentioning
confidence: 90%
“…Therefore, the decision to diagnose malingering should always be based on multiple sources of information. In addition to test findings, some researchers (Bierley et al, 2001;Faust & Ackley, 1998) have indicated that the diagnosis of malingering should be based on evidence that the exaggeration was both intentional and motivated by external incentive. Other researchers (Slick et al, 1999) have indicated that, because intentionality cannot be measured, clinicians should attach probability statements (i.e., ''definite,'' ''probable,'' or ''possible'') to their inferences regarding malingering, and the strength of the probability statement should be reflective of the number and specificity of behavioral indicia that suggest malingering.…”
Section: Discussionmentioning
confidence: 97%
“…The DSM-IV indicates that a factitious disorder should be diagnosed when an examinee intentionally performs poorly in order to assume the sick role. Additionally, exaggerated neuropsychological deficits can occur as a result of unconscious processes such as somatization or depression (Bierley et al, 2001). Therefore, some researchers have argued that the diagnosis of malingering requires evidence of intentionality in addition to evidence of exaggeration (Faust & Ackley, 1998).…”
mentioning
confidence: 99%
“…Indeed, her MMPI-2 scale elevations, in particular 3-2-1, were suggestive of a somatized depression as well. Some authors have posited that, rather than being dichotomous concepts, malingering and somatoform presentations may lie on a continuum between self-deception and other-deception, with some patients embodying elements of both conditions (Bierley et al, 2001). While a primarily somatoform presentation can reasonably be assumed in the presence of a 1-3 MMPI-2 codetype, passed cognitive effort tests, and adoption of the invalid role in daily life activities, and malingering is likely indicated by numerous failed cognitive effort indicators and symptoms only displayed in the examiner's office, more sophisticated techniques, unfortunately not yet available, are needed to accurately determine the relative contribution of conscious and nonconscious contributors to symptom production.…”
Section: Neurocognitive and Psychological Findingsmentioning
confidence: 98%